The Habit of Drinking Tea and Its Association with the Incidence of Anemia among Pregnant Women at West Prabumulih Public Health Center in 2025 - Erwina, Erwina; Komariah, Nurul; Dahliana, Dahliana (Journal of Maternal and Child Health Sciences (JMCHS), 2025)
Background: Pregnant women often face a high risk of developing anemia. This condition is caused by the increased need for iron during pregnancy to support fetal growth and also to meet their own iron needs during pregnancy. Iron is an essential component needed for the formation of hemoglobin and red blood cells in the body. Government programs to overcome anemia include the provision of iron supplements (TTD), balanced nutrition education, iron fortification, cooperation with related parties, health worker training and development of promotional and socialization media. Research Objective: To determine the Relationship between Tea Drinking Habits and the Incidence of Anemia in Pregnant Women at the West Prabumulih Health Center in 2025. Research Method: This research design uses a cross-sectional design, the sampling technique in this study is Accidental sampling. The population in this study were all pregnant women who came and checked/checked Hb at the Prabumulih Barat Health Center in March, namely 94 people, the sample in this study was 94 respondents. The results of the study of the bivariate analysis obtained a p value of 0.000 (<0.05) which means that there is a relationship between tea drinking habits and the incidence of anemia. Conclusion: there is a relationship between tea drinking habits in pregnant women and the incidence of anemia in pregnant women at the Prabumulih Barat Health Center in 2025.